2008
DOI: 10.7202/018954ar
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of host resistance inducers and conventional products for fire blight management in loquat and quince

Abstract: Fire blight disease is one of the most destructive diseases of pome fruits. Due to the lack of effective, non-phytotoxic and publicly acceptable materials for controlling fire blight in pome fruit trees, new strategies to manage Erwinia amylovora fire blight are being sought. The resistance-inducing compounds prohexadione-Ca, harpin protein and benzothiadiazole (acibenzolar-S-methyl), the fertilizer humic acid, the bactericides streptomycin and copper salts, and combinations of copper with chemicals were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…In all the trials, the new formulate IRF 155 (copper oxychloride + copper hydroxide) was one of the most promising products for bacterial disease control, able to reduce the leaf disease symptoms by 70-80 %, compared with the control. Acibenzolar-S-methyl, a functional analogue of salicylic acid, has demonstrated good efficacy against bacterial diseases, including bacterial spot and bacterial speck on tomato (Louws et al 2001) and fire blight in apples (Bastas and Maden 2007). Similar efficacy was provided by acibenzolar-S-methyl against Psa on kiwifruit.…”
Section: Discussionmentioning
confidence: 94%
“…In all the trials, the new formulate IRF 155 (copper oxychloride + copper hydroxide) was one of the most promising products for bacterial disease control, able to reduce the leaf disease symptoms by 70-80 %, compared with the control. Acibenzolar-S-methyl, a functional analogue of salicylic acid, has demonstrated good efficacy against bacterial diseases, including bacterial spot and bacterial speck on tomato (Louws et al 2001) and fire blight in apples (Bastas and Maden 2007). Similar efficacy was provided by acibenzolar-S-methyl against Psa on kiwifruit.…”
Section: Discussionmentioning
confidence: 94%
“…It is known that orchard practices minimizing excessive vegetative growth of trees reduce host plant susceptibility to fire blight. Many growth regulators reducing shoot growth are also used to reduce fire blight intensity (Yoder et al 1999;Bastas and Maden 2007). Hepaksoy et al (1999) observed that fire blight damage progressed more on young and strongly growing shoots of pear trees, and thus these shoots were more susceptible to fire blight.…”
Section: Discussionmentioning
confidence: 98%
“…Harpin has been applied as an effective postharvest treatment to prevent decay in oranges [103], melons [104], apples [105] and pears [106]. In addition, field applications demonstrated its usefulness for controlling pathogen-borne diseases in passion fruits [107], pears [108], quince and loquat [109].…”
Section: Harpinmentioning
confidence: 99%